SOURCES OF HIGH PROTEIN CONTENT IN COMMON BEAN SEEDS (PHASEOLUS VULGARIS) FROM THE VIR COLLECTION - G. P. Egorova; I. N. Perchuk; A. E. Solovyeva; T. V. Buravtseva (Труды по прикладной ботанике, генетике и селекции)
Background. An important trend in modern breeding of common beans is to improve the quality of grain. High protein content in seeds is one of the most important indicators of the nutritional value of beans. Searching for high-protein accessions, identifying sources of high protein content, and using them in the breeding process, while developing new cultivars, still remain relevant. The aims of our research included the identification of variability patterns for protein content in accessions of different origin, characterization of cultivars, and description of their morphological and economic traits.Materials and methods. Presented here are the results of biochemical screening of 166 common bean (Phaseolus vulgaris L.) accessions of various ecogeographic origin, added to the VIR collection in 2005–2016. Field study of economically valuable traits was carried out according to VIR’s techniques. The protein content in seeds was measured in the Biochemistry and Molecular Biology Department at VIR using Kjeldahl method. Mathematical data processing (correlation analysis and single-factor analysis of variance) was performed using Statistica 7.0 software (StatSoft, Inc., USA).Results and conclusions. As a result of the assessment, 12 sources of high protein content in seeds (> 28% annually) were identified and described. The average value of the trait differed depending on the country of origin, genotype and year of study. The correlation analysis failed to find general regularities (strong stable interrelations) between the protein content in seeds and morphological, economically valuable traits. The values of correlation coefficients were unstable over the years of study. Weak links between the protein content and the genotype (r = 0.25) or the year of reproduction (r = 0.24) were identified. Significant relationships between protein content, morphological and economically valuable traits were not found. Seed protein content, according to the results of the single-factor analysis of variance, largely depended on the genetic properties of plants (effect size is 70.1%), and, to a smaller extent, on the year of reproduction (14.5%) and origin (17.5%).